Delegating power? Performance management from a process perspective. Issue 2 (30th December 2020) - Gofen, Anat; Gassner, Drorit
Abstract: In contrast to the well‐documented impacts of implementing performance management (PM) systems, the evolution of PM systems' design is understudied, despite the understanding that PM requires ongoing maintenance, continuing reconsideration, and constant adaption to local circumstances. This study employs a process perspective on PM by focusing on the four generations of the Israeli police PM system implemented from 1999 to 2016. Data are drawn from official documentation and interviews with various stakeholders who were involved in the system's re‐designs. PM evolution emerged as a decentralization process, during which Chiefs were gradually given more power, partially at the expense of top management power, through increased discretion, self‐learning features, enhanced understanding and decoupling of measurement–incentives. Shifting from "one size fits all" to a more "tailor‐made" approach, and from top‐down control to user management, PM decentralization exemplifies constructive efforts to bridge the well‐known gap between policy aims and outcomes in performance‐oriented reforms.